Ovariole number does not predict reproductive output or trade-off with immunity in Drosophila melanogaster - Kiran Adhikari; Fajr Ali; Marco A. Malo Jr; Brian P. Lazzaro (PLoS ONE, 2025)
Reproduction and immunity are two energetically demanding traits that frequently trade-off with each other. Prior studies have suggested that the cost of reproduction limits the ability of Drosophila melanogaster females to fight bacterial infections, including the direct cost of developing and provisioning eggs. Ovariole number is a genetically variable trait in Drosophila, and is frequently assumed to be a good indicator of reproductive capacity. This implies ovariole number might also predict the quality of defense against bacterial infection. Here, we used 13 isogenic lines from the Drosophila Genomic Reference Panel to test whether reproductive investment trades off with immune response. These lines vary genetically for ovariole number, but we found ovariole number is not a predictor of reproductive output in infected females nor of resistance to bacterial infection. Furthermore, we saw no strong genetic tradeoff between fecundity and defense against infection in our experimental framework. Our results suggest that the evolutionary trade-off between reproduction and immunity could be weak, at least when measured in the laboratory, even when the physiological trade-off between these two traits is strong.